Towards Identifying Protective B-Cell Epitopes: The PspA Story - Khan, Naeem; Jan, Arif T. (Frontiers in Microbiology, 2017)
Pneumococcal surface protein A (PspA) is one of the most abundant cell surface protein of Streptococcus pneumoniae (S. pneumoniae). PspA variants are structurally and serologically diverse and help evade complement-mediated phagocytosis of S. pneumoniae, which is essential for its survival in the host. PspA is currently been screened for employment in the generation of more effective (serotype independent) vaccine to overcome the limitations of polysaccharide based vaccines, providing serotype specific immune responses. The cross-protection eliciting regions of PspA localize to the α-helical and proline rich regions. Recent data indicate significant variation in the ability of antibodies induced against the recombinant PspA variants to recognize distinct S. pneumoniae strains. Hence, screening for the identification of the topographical repertoire of B-cell epitopes that elicit cross-protective immune response seems essential in the engineering of a superior PspA-based vaccine. Herein, we revisit epitope identification in PspA and the utility of hybridoma technology in directing the identification of protective epitope regions of PspA that can be used in vaccine research.